An Educational Video Game for Nutrition of Young People: Theory and Design. (August 2016) - Ledoux, Tracey; Griffith, Melissa; Thompson, Debbe; Nguyen, Nga; Watson, Kathy; Baranowski, Janice; Buday, Richard; Abdelsamad, Dina; Baranowski, Tom
Background. Playing Escape from Diab (DIAB) and Nanoswarm (NANO), epic video game adventures, increasedfruit andvegetable consumption among amulti-ethnic sample of 10-12 year oldchildren duringpilot testing. Key elements of both games were educationalmini-games embedded in the overall game that promotedknowledge acquisition regarding diet, physical activity andenergy balance . 95-100% of participants demonstrated mastery of these mini-games suggesting knowledge acquisition. Aim. This article describes the process ofdesigning and developing the educationalmini-games . A second purpose is to explore theexperience of children while playing the games. Method. The educational games were based onSocial Cognitive andMastery Learning Theories. A multidisciplinary team ofbehavioral nutrition, PA, and video game experts designed, developed, and tested the mini-games. Results. Alpha testing revealed children generallyliked the mini-games and found them to be reasonablychallenging . Process evaluation data from pilot testing revealed almost all participantscompleted nearly all educational mini-games in a reasonable amount of time suggestingfeasibility of this approach. Conclusions. Future research should continue to explore the use of video games in educating children to achievehealthy behavior changes .